Equality before the Law Principle in the Implementation of Legal Aid in Indonesia - Bramantara, Rezal Helwin (Faculty of Law Universitas Negeri Semarang, 2021)
Legal aid is a legal service provided to the beneficiaries of legal aid according to Law No. 18 of 2003 on Advocates. Considering there are still many people who do not understand that in Indonesia there is also legal aid provided by lawyers at no cost. The ineffectiveness of the application in providing legal aid in Indonesia is a legal issue that is interesting to study more in order to determine the main problems causing lack of effectiveness in the provision of legal aid in Indonesia, which will look for solutions from an idea into a formulation as optimization of legal aid in Indonesia. The issue will be seeking legal issues in the implementation of judicial assistance and formulation of how the application of legal aid may be optimized. This article reviews the development of legal aid as legal services provided by lawyers to people who are not able to freely in Indonesia.